Enhancing Critical Thinking Skills in Science Education Through a Local Wisdom-Based E-Module: An Inquiry-Based Learning Approach - Tia Sarawati; Ismail Fikri Natadiwijaya (Scientiae Educatia: Jurnal Pendidikan Sains, 2025)
Science education has historically relied on conventional teaching materials that are frequently disconnected from students' local cultural contexts, thereby diminishing learner engagement and undermining the contextual authenticity of the science learning experience. Furthermore, although the Inquiry-Based Learning (IBL) model has been widely recognized as an effective pedagogical framework for cultivating critical thinking skills in science education, its implementation within culturally responsive instructional contexts that meaningfully integrate local wisdom remains considerably underexplored in the existing literature. This study aims to analyze the implementation of a local wisdom-based e-module, developed in the context of the natural dyeing process of Mega Mendung batik, within the IBL framework, and to evaluate its effectiveness in enhancing eighth-grade students' critical thinking skills in science learning. A pre-experimental research design with a one-group pretest-posttest configuration was employed. The research sample comprised 32 eighth-grade students selected through random sampling. Data were collected using a validated critical thinking skills assessment instrument aligned with science learning objectives, and subsequently analyzed using a paired sample t-test and effect size calculation to determine the magnitude and practical significance of the instructional intervention. The findings demonstrate that the implementation of the local wisdom-based e-module significantly enhanced students' critical thinking skills across all assessed indicators, with an effect size classified within the high category. These results collectively affirm that science learning mediated through culturally contextualized, local wisdom-based e-modules within the IBL framework constitutes a promising and empirically supported pedagogical strategy for fostering critical thinking in science education. This study further offers practical guidance for science educators and curriculum developers engaged in designing culturally responsive, inquiry-based instructional materials for middle school science contexts.